1995
DOI: 10.1159/000223118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PEEP Ventilation on Liver Metabolism

Abstract: Objective: To study the influence of positive endexpiratory pressure (PEEP) ventilation on metabolic parameters with specific regard to liver metabolism. Design: Prospective experimental study on the effects of PEEP ventilation on nemo-dynamic gas exchange as well as metabolic parameters i. e. hepatic glucose production, arterial, hepatic and portal venous insulin, glucagons, free fatty acid (FFA), glycerol β-hydroxybutyrate and lactate concentrations. Setting: Experimental Laboratory Unit of the University Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Furthermore, in a study by Schricker et al [ 78 ], it was found that PEEP affected liver metabolism by promoting hepatic gluconeogenesis and enhancing oxidative hepatic lipid utilization for energy coverage in the liver[ 78 ]. A parallel increase in the splanchnic oxygen extraction rate was reported in response to a decline in hepatic oxygen delivery caused by a PEEP-dependent decrease in cardiac output[ 78 ].…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a study by Schricker et al [ 78 ], it was found that PEEP affected liver metabolism by promoting hepatic gluconeogenesis and enhancing oxidative hepatic lipid utilization for energy coverage in the liver[ 78 ]. A parallel increase in the splanchnic oxygen extraction rate was reported in response to a decline in hepatic oxygen delivery caused by a PEEP-dependent decrease in cardiac output[ 78 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Furthermore, in a study by Schricker et al [ 78 ], it was found that PEEP affected liver metabolism by promoting hepatic gluconeogenesis and enhancing oxidative hepatic lipid utilization for energy coverage in the liver[ 78 ]. A parallel increase in the splanchnic oxygen extraction rate was reported in response to a decline in hepatic oxygen delivery caused by a PEEP-dependent decrease in cardiac output[ 78 ]. This mechanism has been corroborated by various human studies which have shown that increasing levels of PEEP reduced splanchnic blood flow, thereby jeopardizing oxygen delivery to the abdominal viscera; yet, splanchnic oxygen consumption was usually maintained through a compensatory increase in splanchnic oxygen extraction[ 79 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Brienza et al1 showed that PEEP ventilation decreased the total venous return, probably through an increase in the venous back pressure at the outflow end of the liver, and a decrease in the portal vein flow. A study by Schricker et al2 revealed that PEEP ventilation increased hypoxia of the liver. These studies engendered concern that PEEP ventilation might adversely affect a newly transplanted liver.…”
Section: Commentsmentioning
confidence: 99%